2022
DOI: 10.3390/electronics11050788
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Determining Quality Requirements for Mobile Learning Applications Using Delphi Method

Abstract: The development of mobile learning apps might fail due to poor selection of the suitable technical requirements for mobile devices. This will affect the quality of mobile learning applications and, thus, will increase the development cost of mobile learning apps. Due to the above issues, we need to determine the most appropriate technical quality requirements for the development of mobile learning apps that meet user requirements. To achieve that, we propose a comprehensive framework to capture the most suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 36 publications
4
74
0
2
Order By: Relevance
“…However, those responses with less than 15% missing data were treated by replacing the missing values with the mean ones, as Jenkins et al [ 20 ] suggested. Subsequently, the data were analyzed using the method outlined in [ 20 , 21 , 44 , 45 ]. The screening process has brought the final sample to 345 valid responses.…”
Section: Resultsmentioning
confidence: 99%
“…However, those responses with less than 15% missing data were treated by replacing the missing values with the mean ones, as Jenkins et al [ 20 ] suggested. Subsequently, the data were analyzed using the method outlined in [ 20 , 21 , 44 , 45 ]. The screening process has brought the final sample to 345 valid responses.…”
Section: Resultsmentioning
confidence: 99%
“…Facilitating conditions, which refer to students' self-efficacy as well as to what extent the proper organizational and technical infrastructure required for the support m-learning process exists, is also expected to influence students' decision to continue use m-learning. Prior m-learning studies highlighted the importance of examining the effect of facilitating condition on students' behavioral intention to use m-learning (Al-Hujran et al, 2014;Jeong et al, 2019;Thomas et al, 2013), including students capabilities or self-efficacy (Al-Hujran et al, 2014), the universities top management support (Almaiah and Almulhem, 2018), the availability of stable Internet accessibility and connection quality (Nassr et al, 2020), and necessary hardware and software for adopting e-learning system (Almaiah et al, 2020). The role of self-efficacy of students is greatly reported in e-learning studies (Abdullah and Ward, 2016;Almaiah et al, 2020).…”
Section: The Unified Theory Of Acceptance and Use Of Technology Factorsmentioning
confidence: 99%
“…The instructors readiness, capability, confidence level and competencies including online technological, communication and teaching skills are critical on creating more successful online learning experience and thus shaping students satisfaction and positive intention to continue its use (Cole et al, 2017;Easton, 2003;Martin et al, 2019). Weak IT skills of faculty members negatively impact the effectiveness of e-learning process (Almaiah et al, 2020;Almaiah and Almulhem, 2018). The instructor's ability, behavior and performance toward facilitating the collaborative learning during online learning is critical success factors of e-learning process (Guasch et al, 2010;Turhangil Erenler, 2020).…”
Section: Instructors' Online Teaching Competencies and Student's Soci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Eltahir ( 2019 ) established that the challenges of e-learning in developing countries remain a reality due to the digital divide in existence. Other studies have also found serious challenges of technological infrastructure in developing countries including lack of computers in HEIs to serve students all the time (Alsabawy et al, 2013 ; Al-Araibi et al, 2019 ; Al-Azawei et al, 2016 ; Alkharang, 2014 ; Almaiah & Almulhem, 2018 ; Almaiah & Alyoussef, 2019 ; Al-Araibi et al, 2019 ; Aung & Khaing, 2016 ; Barteit et al, 2019 ; Eltahir, 2019 ; Esterhuyse & Scholtz, 2015 ; Geduld, 2013 ; Igbokwe et al, 2020 ; Lwoga, 2014 ; Lwoga & Komba, 2015 ; Kenan et al, 2014 ; Kisanga & Ireson, 2015 ; Mtebe & Raisamo, 2014b ; Makokha & Mutisya, 2016 ; Moakofhi et al, 2017 ; Munezero et al, 2016 ; Naresh & Reddy, 2015 ; Naveed et al, 2017a , 2017b ; Nwabufo et al, 2013 ; Pani et al, 2015 ; Rana et al, 2014 ; Sanga et al, 2013 ; Sayed & Baker, 2014 ; Siemens et al, 2015b ; Tarus & Gichoya, 2015 ; Tarus et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%